Density functional theory study of Chlorine, Fluorine, Nitrogen, and Sulfur doped rutile TiO2 for photocatalytic application - Fikadu Takele Geldasa; Francis Birhanu Dejene; Mesfin Abayneh Kebede; Fekadu Gashaw Hone; Edosa Tasisa Jira (Scientific Reports)
Abstract This study uses the Quantum ESPRESSO code to introduce Hubbard correction (U) to the density functional theory (DFT) in order to examine the effects of non-metals (C, F, N, and S) doping on the structural, electronic, and optical characteristics of rutile TiO2. Rutile TiO2 is a substance that shows promise for use in renewable energy production, including fuels and solar energy, as well as environmental cleanup. Its wide bandgap, however, restricts their uses to areas with UV light. In order to move the rutile TiO2 absorption edge toward visible light, one atom of each dopant was substituted at oxygen atom locations in this work. The calculated band structures yielded a bandgap of 3.03 eV for pure rutile TiO2, which is in good agreement with the experimental measurement. The bandgap of all doped materials, with the exception of F-doped TiO2, displayed a redshift. The absorption edges in C, N, and S-doped TiO2 are displaced toward the visible area, as indicated by the imaginary component of the dielectric function peaks. The appropriateness of C, N, and S-doped TiO2 for photocatalysis applications is demonstrated by the shift in the absorption coefficient to the highest wavelength. The presence of extra charges that attenuate the transmission of light in materials is shown by the increase in refractive index following doping. Furthermore, this discovery is crucial for experimentalists since it helps them understand how non-metal doping affects the characteristics of rutile TiO2 for photocatalysis applications.